Blood Biochemical Indices and Productivity of Broilers on Diet Supplemented with Mannan Oligosacharide, Baker Yeast, or Combined Baker Yeast and Noni Leaves Extracts - Murwani , Retno; Indriani, Anantasia; Yuliana, Iyan; Wihardani, Kinanthi; Wahyuningrum, Maria Aditia; Tawakal, Nur Rendra; Mulyono; Kusumanti, Endang (International Journal of Poultry Science, 2011)
A research was carried out to study the inclusion of MOS, inactivated baker yeast or combined baker yeast and Noni leaves extracts into corn-mungbean basal diet on broilers blood biochemical indices and productivity. Lohman MB-202 day old chicks were randomly assigned into four treatment diets i.e. 1) commercial/control diet (Dc), 2) basal diet plus MOS (DM), (3) basal diet plus inactivated baker yeast (DY), (4) basal diet plus inactivated baker yeast and Noni leaves extracts (DY+L). Treatment diets and water were given ad libitum. Whole blood were sampled on day 21 for determination of hemoglobin and haematocrit, Serum Glutamic Pyruvic Transaminases, Glutamic Oxaloacetic Transaminases, creatinine, lipid profile, alkaline phosphatase and lactic acid. Relative organs weight, abdominal fat, productivity were also determined. Feed intake, body weight and feed conversion of broilers fed DM, DY, DY+L were the same but they were lower than control diet (p<0.05). Serum triglyceride, GPT, creatinine, cholesterol, VLDL+LDLchol and HDLchol were significantly affected by the diets (p<0.05). No effect was found for other serum biochemical indices. For relative internal organs weight, a significant effect was found for heart, liver, ileum, duodenum and pancreas. These results were discussed in terms of the possible underlying mechanism. Our results here provide evidence that MOS, inactivated baker yeast alone or its combination with Noni leave extract could produce low serum TG, total cholesterol, VLDL+LDLchol, HDLchol and abdominal fat in broilers fed corn-mungbean basal diet with no negative effect on other serum biochemical indices.